2014
DOI: 10.5539/ibr.v7n2p53
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Relationship between Liquidity Risk and Market Risk with Non-Ordinary Return at Fama—French Three Factor Model at Tehran Stock Exchange

Abstract: Each financial market in compliance with broadness and depth has several diverse tools for making investment and investors make investment according to return and asset risk. There are different types of risk and investors due to each of them demand for taking risk. In this research, the effect of information quality is studied by regarding liquidity risk, effect of information quality by regarding risk of market on non-ordinary return at Fama-French three model factor. In this research the stock return influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Along with this, Hamid, Hanif, Malook, and Wasimullah (2012) indicated that FF explained many variations in returns in Pakistan firms. Tackling this issue in Tehran, Shams et al (2014) showed that the influence of size and value factors was eliminated. Investigating this issue in Vietnam, Hoang et al (2013) found that FF1993 model are superior to CAPM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along with this, Hamid, Hanif, Malook, and Wasimullah (2012) indicated that FF explained many variations in returns in Pakistan firms. Tackling this issue in Tehran, Shams et al (2014) showed that the influence of size and value factors was eliminated. Investigating this issue in Vietnam, Hoang et al (2013) found that FF1993 model are superior to CAPM.…”
Section: Literature Reviewmentioning
confidence: 99%